The Impact Of Climate Change On Agriculture In Indonesia And Its Strategies: A Systematic Review - Hafidha Asni Akmalia (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Agriculture in a time of climate change is very wary of various countries in the world because it can threaten food security. Indonesia faces this problem based on data and reported news. This paper aims to provide some information about the potential threats of climate change towards crop production in Indonesia to initiate innovations that can be done to maximize crop production amid climate change. We compile this literature review to develop thoughts related to adaptation strategies undertaken to maximize the productivity of food crops under climate change, especially in Indonesia. Several studies that were reviewed showed that there was a decrease in food crop production due to factors in the environment that were changing because of climate change. Therefore, the provided strategy is an example that can be applied and developed to maintain national food productivity. Continued research is needed to provide other plans that are integrated with existing strategies.